2019
DOI: 10.1038/s41418-019-0304-y
|View full text |Cite|
|
Sign up to set email alerts
|

Long noncoding RNA LINC00336 inhibits ferroptosis in lung cancer by functioning as a competing endogenous RNA

Abstract: The regulatory loop between long noncoding RNAs (lncRNAs) and microRNAs has a dynamic role in transcriptional and translational regulation, and is involved in cancer. However, the regulatory circuitry between lncRNAs and microRNAs in tumorigenesis remains elusive. Here we demonstrate that a nuclear lncRNA LINC00336 is upregulated in lung cancer and functions as an oncogene by acting as a competing endogenous RNA (ceRNAs). LINC00336 bound RNA-binding protein ELAVL1 (ELAV-like RNA-binding protein 1) using nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
346
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 445 publications
(350 citation statements)
references
References 51 publications
3
346
0
1
Order By: Relevance
“…MicroRNA-137 plays a novel and indispensable role in ferroptosis by inhibiting glutaminolysis , and at the same time, microRNA-9 was demonstrated regulating ferroptosis by targeting glutamic-oxaloacetic transaminase 1 (GOT1) . Long non-coding RNA LINC00336 served as an endogenous sponge of microRNA-6852 (MIR6852) to regulate the expression of cystathionine-β-synthase (CBS), and MIR6852 directly binds to LINC0036 and serves as a negative upstream regulator of CBS-mediated ferroptosis inhibition (Wang et al, 2019c).…”
Section: Some News Finding For Ferroptosis Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNA-137 plays a novel and indispensable role in ferroptosis by inhibiting glutaminolysis , and at the same time, microRNA-9 was demonstrated regulating ferroptosis by targeting glutamic-oxaloacetic transaminase 1 (GOT1) . Long non-coding RNA LINC00336 served as an endogenous sponge of microRNA-6852 (MIR6852) to regulate the expression of cystathionine-β-synthase (CBS), and MIR6852 directly binds to LINC0036 and serves as a negative upstream regulator of CBS-mediated ferroptosis inhibition (Wang et al, 2019c).…”
Section: Some News Finding For Ferroptosis Regulationmentioning
confidence: 99%
“…Ferroptosis is characterized by the massive accumulation of fatal intracellular lipid reactive oxygen species (ROS) when the antioxidant capacity of cells decreases (Dixon et al, 2012). Studies have found that ferroptosis is regulated by GPX4 (system Xc-) (Dixon et al, 2012;Friedmann Angeli et al, 2014;Yang et al, 2014), lipid synthesis Gao and Jiang, 2018), iron metabolism (Gao et al, 2016;Hou et al, 2016;Hassannia et al, 2019), the mevalonate pathway (Shimada et al, 2016), Nrf2 (or NFE2L2) pathway (Abdalkader et al, 2018;Kerins and Ooi, 2018), and other factors Wang et al, 2019c;Ye et al, 2019). Among them, the regulatory effect of transcription factor nuclear factor E2 related factor 2 (Nrf2/NFE2L2) on ferroptosis has attracted our interest.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs have been reported to participate in the progression of various types of tumors, including lung cancer . For example, Yu et al .…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA LINC01551 has been found to upregulate cellular proliferation and migration in non-CNS cancers such as hepatocellular carcinoma by interacting with the miR122-ADAM10 axis [60]. LINC00336 promoted lung cancer progression by inhibiting regulated cell death by knocking down miR-6852 function [61].…”
Section: Discussionmentioning
confidence: 99%